Strategi Implementasi Teori Manajemen Gereja untuk Pertumbuhan Jemaat - Gladys Ansye Rangian; Beni Chandra Purba; Budi Kelana (PT. Penerbit Tiga Mutiara, 2024)
Congregational growth and spiritual development of church members are the primary goals of every religious community. However, the challenges faced by the church today are not solely limited to spiritual aspects but also consider management aspects that support healthy and sustainable growth. This paper aims to investigate the implementation strategies of church management theory as an effort to advance congregation growth and enhance individual spiritual quality. The research method used is a descriptive qualitative approach, allowing researchers to delve into the complexity of social situations influencing church growth. By combining data from various sources, including books, scholarly articles, and academic journals, the author presents key principles of church management theory, such as shared leadership, humility, and resource management effectiveness. Furthermore, this paper discusses factors influencing congregational growth, including the significant role of prayer, discipleship, fellowship, and testimony in shaping enthusiastic and committed communities. By applying appropriate strategies supported by strong leadership, churches can achieve meaningful and spiritually significant growth, strengthening the foundation of faith and expanding their influence in society. Thus, this paper provides a comprehensive view of the importance of integrating management theory within the church context and offers practical guidance for churches to reinforce growth and spiritual development efforts.